The effect of lithium salt type on ionic conductivity of poly(vinylidene difluoride)-based solid polymer electrolytes. (2nd July 2020) - Jeong, Min Ung; Goh, Yumin; Kwon, Do-Kyun; Choi, U Hyeok
Abstract: Recently, research on solid polymer electrolytes (SPEs) for lithium-ion batteries (LIBs) has been actively carried out as an alternative to conventional liquid electrolytes that present safety issues such as flammability and explosion. However, the SPEs show relatively low ion conductivity, compared to the liquid electrolytes. In this study, a poly(vinylidene difluoride) (PVDF)-based SPE was prepared by introducing two different electrolytes; one is weak-binding lithium bis(trifluoromethane)sulfonimide (LiTFSI) salt mixture with solvating plastic crystal succinonitrile (SN) and the other is lithium bis(fluorosulfonyl)imide (LiFSI) salts. Among the SPEs studied, the PVDF/LiFSI-containing SPE membrane exhibited the highest room temperature ion conductivity of 1 x 10 −3 S/cm, characterized by electrochemical impedance spectroscopy (EIS).